The Christianization of African Traditional Religions - Turaki, Yusufu (International review of mission, 2019)
In studies of the historical growth and spread of Christianity in Africa, the focus has been too much on Christianizing African social and religious institutions and structures, and not enough on African traditional religion itself, which needs to be addressed by Christianity. This article addresses the core - that is, the theology and worldview - of the African traditional religion. It argues that this core needs to be Christianized and shows how this can be done. In order to achieve this task, the article uses a new theological method, a "systematic theology" of African traditional religion, as the basis for a theological method of engagement and interaction of religions and worldview. This new method explains in practical terms how Christianity can effectively Christianize African traditional religions and worldviews.